Evaluation of Andrographis paniculata in a mouse model of influenza A viral infection using oral administration and a translationally relevant dose - Shamim, Kashif; Burnett, Grace C.; Zhang, Jin; Ahmed, Nessma H.; Khan, Shabana I.; Chittiboyina, Amar G.; Khan, Ikhlas A.; Marshall, Gailen D.; Bates, John T.; Pugh, Nirmal D. (Frontiers in Pharmacology, 2026)
IntroductionEthnobotanically, Andrographis paniculata aerial parts have been used to alleviate the symptoms of viral infections, colds, and sore throats. Although the utility of Andrographis for these indications has had widespread acceptance, multiple knowledge gaps, regarding mechanisms and specific clinical applications, exist for this botanical. Prior rodent studies have limited applicability to inform future clinical applications due to routes of administration used, nonclinical high doses tested, and exclusive evaluation of chemically purified compounds.MethodsExperiments used a commercial extract of A. paniculata manufactured from aerial parts that was standardized to contain ≥10% andrographolides. In vitro evaluation measured NF-κB in THP-1 monocytes, iNOS in RAW 264.7 macrophages and Nrf2 in HepG2 cells. In vivo research used a non-lethal influenza A mouse model with two groups (A. paniculata treatment and vehicle control). Following infection, mice were gavaged daily for 8 days–treatment group received 250 mg extract/kg body weight (dose equivalent to the human label-recommended daily intake).ResultsThe extract inhibited NF-κB and iNOS while activating Nrf2. Although andrographolide contributed to these effects, the findings indicate the presence of additional active constituents that have not yet been characterized. In the mouse model, oral administration of the extract produced a roughly five-fold reduction in lung viral load by day 3 post-infection (p < 0.021) compared with control animals.DiscussionBased on the clinically relevant design of our mouse model, the results lay the groundwork for future preclinical research to determine optimal treatment schedule/dosage and immune mechanisms, thereby informing the design for future resilience efficacy clinical trials.